2009
DOI: 10.2131/jts.34.sp287
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine environment-genome interaction and Children's development (3): Assisted reproductive technologies and developmental disorders

Abstract: -In vitro fertilization (IVF) and other assisted reproductive technologies (ART) are widely used clinically as infertility treatments. Although ART procedures are generally considered safe, some studies have suggested an increase in the occurrence of major malformations and some other complications in babies conceived by ART. Further, it has recently been suggested that ART are associated with imprinting disorders in the offspring such as Beckwith-Wiedemann syndrome and Angelman syndrome. We review the human a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…We already know that the incidence of birth defects following assisted conception is double that seen in the naturally conceived population 11 and that imprinting disorders, notably the BeckwithWiedemann and Angelman syndromes, seem to be increased in such children. 12 Infants conceived by ART are also significantly more likely to be admitted to a neonatal intensive care unit, to be hospitalized and to stay in hospital longer than their naturally conceived counterparts. 13 Recent studies have also shown an increase in the hospitalization of ART offspring in infancy and early childhood compared with spontaneously conceived children, [14][15][16] whereas other investigations have revealed abnormal retinal vascularization and an eightfold increase in the incidence of undescended testicles in boys conceived by ICSI.…”
Section: Introductionmentioning
confidence: 99%
“…We already know that the incidence of birth defects following assisted conception is double that seen in the naturally conceived population 11 and that imprinting disorders, notably the BeckwithWiedemann and Angelman syndromes, seem to be increased in such children. 12 Infants conceived by ART are also significantly more likely to be admitted to a neonatal intensive care unit, to be hospitalized and to stay in hospital longer than their naturally conceived counterparts. 13 Recent studies have also shown an increase in the hospitalization of ART offspring in infancy and early childhood compared with spontaneously conceived children, [14][15][16] whereas other investigations have revealed abnormal retinal vascularization and an eightfold increase in the incidence of undescended testicles in boys conceived by ICSI.…”
Section: Introductionmentioning
confidence: 99%
“…Children conceived through these technologies are at increased risk of low birth weight, premature birth, malformations, and genomic imprinting disorders (10)(11)(12)(13)(14)(15). Currently, little is known about the effects of preovulatory aging of oocytes, and the causal relationship between impaired oocyte quality because of intrafollicular overripeness and developmental defects remains elusive.…”
mentioning
confidence: 99%
“…Furthermore, epigenetic chromatin remodeling is believed to be required to produce a totipotent embryo. Epigenetic events also happen during fertilization when maternal and paternal DNA undergo demethylation in a sex-specific manner (Laprise, 2009;Shiota and Yamada, 2009). Successive cell divisions are characterized by acetylation, methylation, and phosphorylation but the effects of such modifications are unclear.…”
Section: Epigenetics and Early Developmentmentioning
confidence: 99%